2013
DOI: 10.15288/jsad.2013.74.288
|View full text |Cite
|
Sign up to set email alerts
|

Where and When Adolescents Use Tobacco, Alcohol, and Marijuana: Comparisons by Age, Gender, and Race

Abstract: ABSTRACT. Objective: This study examined the location and time of adolescent use of cigarettes, alcohol, and marijuana. Age, gender, and racial differences in location and time of use were studied for each substance. Method: Using cross-sectional data collected through the schoolwide Pride Survey, 20,055 students between the ages of 10 and 19 years (53.6% female, 55.1% Black, 44.9% White) in one metropolitan area reported on their frequency of cigarette, alcohol, and marijuana use, as well as the location and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
45
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(60 citation statements)
references
References 48 publications
10
45
0
2
Order By: Relevance
“…ESPAD researchers and other authors [1,2,5] appointed great importance of gender differences. ESPAD surveys from 1995 showed that all illicit drugs, and particularly cannabis, were more often used in boys than in girls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ESPAD researchers and other authors [1,2,5] appointed great importance of gender differences. ESPAD surveys from 1995 showed that all illicit drugs, and particularly cannabis, were more often used in boys than in girls.…”
Section: Discussionmentioning
confidence: 99%
“…Authors from different countries found that cannabis products abuse leads to the same adverse effects as of other illicit drugs [3][4][5][6]. The regular use of cannabis products is associated with an increase of the incidence in mental disorders for young people [7].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the purpose of this study was to examine the relationship between ESE and alcohol and tobacco use in a large cross-sectional adolescent sample from South Carolina. In accordance with prior studies that focus on both race and gender, and given differences in tobacco, alcohol, and other drug use between races/genders, as highlighted by Goncy & Mrug (2013) and in previous adolescent ESE research (Valois et al, 2008;Valois, Zullig, Kammermann, et al, 2013), four race/gender groupings were explored in this study: Black males, Black females, White males, and White females. In this study, it was hypothesized that relationships between ESE and alcohol and tobacco use would exist and vary among the selected race/gender groups.…”
mentioning
confidence: 96%
“…Furthermore, numerous differences in substance use have been associated with certain demographics (such as gender and race), including time of usage and location for usage (Goncy & Mrug, 2013).…”
mentioning
confidence: 99%
“…Crnci najčešće konzumiraju alkohol kod kuće, u školi, u autu, posle škole i noću tokom vikenda, a takođe često koriste marihuanu u školi. 22 Upoređivanjem istraživanja sprovedenih u različitim državama i društvima, otkrivaju se kulturni aspekti, identikuju se značajne sličnosti i razlike kada je u pitanju adolescentna upotreba psihoaktivnih supstanci. Ne treba zanemariti da pažljivo proučavanje studija doprinosi pronalaženju rešenja za već spomenuti problem i uočavanju promena u oblasti vezanoj za adolescnetnu upotrebu supstanci.…”
Section: Pas Kao Globalni Problemunclassified